Self-Presentation of Generation Z’s Interpretation on Linkedin - Muhammad Fauzan Hazami; Siti Khumayah; Aghnia Dian Lestari (International Journal Labs, 2026)
The development of professional social media has made Generation Z more active in building their own identity in the digital space, especially through LinkedIn as a career-focused platform. Some previous research has addressed personal branding and digital identity for Generation Z, but most still discuss social media in general and have not specifically examined how the meaning of professional identity is shaped and displayed on LinkedIn. This research aims to find out how Generation Z interprets LinkedIn as a medium for forming professional identities, how they present themselves, and what the meaning of the digital activities they do. This study used a descriptive qualitative approach with in-depth interview techniques and observations of LinkedIn accounts of users aged 18-28 years. The data was analyzed through the process of reduction, grouping, and interpretation of meaning based on virtual identity theory, personal branding, and symbolic interaction. The results of the study show that LinkedIn is understood as an important space to build a professional image through the management of profiles, experiences, and interactions that are in accordance with work norms. The identity displayed is the result of an adjustment between self-authenticity and the demands of professionalism in the digital world.